2015
DOI: 10.18632/oncotarget.6380
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants inMLLconfer to bladder cancer recurrence identified by whole-exome sequencing

Abstract: Bladder cancer (BC) is distinguished by high rate of recurrence after surgery, but the underlying mechanisms remain poorly understood. Here we performed the wholeexome sequencing of 37 BC individuals including 20 primary and 17 recurrent samples in which the primary and recurrent samples were not from the same patient. We uncovered that MLL, EP400, PRDM2, ANK3 and CHD5 exclusively altered in recurrent BCs. Specifically, the recurrent BCs and bladder cancer cells with MLL mutation displayed increased histone H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…In addition, ARID1A , which encodes for a component of the SWI/SNF chromatin-remodeling complex, is altered in 22% of bladder tumors, while MLL2 , which encodes for an H3K4 methylase, is altered in 17% of bladder cancer patients [18]. Wu et al [82] reported that mutations in MLL, EP400 (a component of the NuA4 histone acetyltransferase complex) and PRDM2 (a nuclear histone/protein methyltransferase) are associated with bladder cancer relapse. MLL mutations in recurrent bladder cancers result in elevated H3K4me3 levels and increased expression of GATA4 and ETS1 [82].…”
Section: Epigenetic Aberrations In Bladder Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ARID1A , which encodes for a component of the SWI/SNF chromatin-remodeling complex, is altered in 22% of bladder tumors, while MLL2 , which encodes for an H3K4 methylase, is altered in 17% of bladder cancer patients [18]. Wu et al [82] reported that mutations in MLL, EP400 (a component of the NuA4 histone acetyltransferase complex) and PRDM2 (a nuclear histone/protein methyltransferase) are associated with bladder cancer relapse. MLL mutations in recurrent bladder cancers result in elevated H3K4me3 levels and increased expression of GATA4 and ETS1 [82].…”
Section: Epigenetic Aberrations In Bladder Cancermentioning
confidence: 99%
“…Wu et al [82] reported that mutations in MLL, EP400 (a component of the NuA4 histone acetyltransferase complex) and PRDM2 (a nuclear histone/protein methyltransferase) are associated with bladder cancer relapse. MLL mutations in recurrent bladder cancers result in elevated H3K4me3 levels and increased expression of GATA4 and ETS1 [82]. Interestingly, MLL3 , which also encodes for an H3K4 methylase, is exclusively mutated in primary tumors, suggesting distinct histone modification signatures between primary and recurrent tumors [82].…”
Section: Epigenetic Aberrations In Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The correction or deletion of resistance‐related genes is a promising development for tumor therapy. Current studies on drug resistance of tumor cells using CRISPR/Cas9 in lung cancer, breast cancer, melanoma, urogenital tumors, and gastrointestinal tumors about chemotherapy drugs, targeted drugs, and inhibitors were summarized in Table . Besides the above‐mentioned studies, there are other studies on the mechanisms related to drug resistance of other malignant tumors cells by using CRISPR/Cas9.…”
Section: Using Crispr/cas9 In the Study Of Tumor Therapiesmentioning
confidence: 99%
“…Current studies on drug resistance of tumor cells using CRISPR/Cas9 in lung cancer, breast cancer, melanoma, urogenital tumors, and gastrointestinal tumors about chemotherapy drugs, targeted drugs, and inhibitors were summarized in Table 2. 56,88,94,97,100,113,[141][142][143][144][145][146][147][148][149][150][151][152][153][154][155] Compared with wild-type cells, ATG5 KO cells had stronger migration ability and significantly increased resistance to the Src tyrosine kinase inhibitor PP2. 156 The results showed that autophagy deficiency can induce malignant cell transformation and resistance to PP2.…”
Section: Drug Resistance Study Of Tumorsmentioning
confidence: 99%